Connection Between Foreshock Structures and the Generation of Magnetosheath Jets: Vlasiator Results. Issue 20 (20th October 2021) - Suni, J.; Palmroth, M.; Turc, L.; Battarbee, M.; Johlander, A.; Tarvus, V.; Alho, M.; Bussov, M.; Dubart, M.; Ganse, U.; Grandin, M.; Horaites, K.; et al.
Abstract: Earth's magnetosheath consists of shocked solar wind plasma that has been compressed and slowed down at the Earth's bow shock. Magnetosheath jets are pulses of enhanced dynamic pressure in the magnetosheath. Jets have been observed by numerous spacecraft missions, but their origin has remained unconfirmed, though several formation mechanisms have been suggested. In this study, we use a method for automatically identifying and tracking jets as well as foreshock compressive structures (FCSs) in four 2D runs of the global hybrid‐Vlasov simulation Vlasiator. We find that up to 75% of magnetosheath jets are caused by FCSs impacting the bow shock. These jets propagate deeper into the magnetosheath than the remaining 25% of jets that are not caused by FCSs. We conduct a visual case study of one jet that was not caused by FCSs and find that the bow shock was not rippled before the formation of the jet. Plain Language Summary: The space around Earth is filled with plasma, the fourth state of matter. Earth's magnetic field shields our planet from the stream of plasma coming from the Sun, the solar wind. The solar wind plasma is slowed down at the Earth's bow shock, before it flows against and around the Earth's magnetic field in the magnetosheath. Sometimes, pulses of high density or velocity can occur in the magnetosheath that have the potential to disturb the inner regions of near‐Earth space where many spacecraft orbit. We call these pulses magnetosheath jets. Magnetosheath jets have been observed by many spacecraft over the past few decades, but how they form has remained unclear. In this study, we use the Vlasiator model to simulate plasma in near‐Earth space and investigate the origins of magnetosheath jets. We find that the formation of up to 75% of these jets can be explained by compressive structures in the foreshock, a region populated by intense wave activity extending sunward of the quasi‐parallel bow shock, where interplanetary magnetic field lines allow shock‐reflected particles to travel back toward the Sun. Key Points: We investigated magnetosheath jets in four hybrid‐Vlasov simulation runs with different solar wind parameters Foreshock compressive structures can explain the formation of up to 75% of magnetosheath jets The foreshock compressive structure‐caused jets travel deeper into the magnetosheath than the 25% of the jets whose origins remain unclear